The Effect of Think Pair Share (TPS) Technique to Improve Students’ Writing Skill on Descriptive Text at Tenth Grade Of SMAN 2 Kab. Tangerang in Academic Year 2018/2019 - Abidah, Mahraodatul; Sabur, Ambuy (Foremost Journal, 2020)
ABSTRACT This research was conducted to find out the effectiveness of Think Pair Share (TPS) technique to teach Students' Writing Skill in Descriptive Text at Tenth Grade Students of SMAN 2 Kab Tangerang. The aim of this research is to find out the significant effect of Think Pair Share (TPS) technique to improve Students' Writing Skill in Descriptive Text at Tenth Grade Students of SMAN 2 Kab Tangerang. The population of this research was Tenth Grade Students of SMAN 2 Kab Tangerang. The writer took the homogeneity two classes namely first experimental class using think pair share technique with 33 students as the sample and control class without using think pair share technique with 35 students as the sample. This research used quasi experimental group - non-equivalent control group design. The writer used pre-test and post-test to get the data. The pre-test was given before treatment while post-test was given after treatments for both classes. Based on the result of this research, the writer took conclusion there are some significant differences between experimental and control class. The average score for the experimental class was 65.33 for the pre-test and 70.67 for the post-test. While the average score for the control class was 64.057 for the pre-test and 67.23 for the post-test. It means that there is an improvement of the students' achievement in writing descriptive texts. Each class has different achievement. The achievement of the experimental class is higher than the control class. In the result of post-test of experimental class was 70.67 which where higher than the control class 67.23. It means that writing a descriptive text by using Think Pair Share (TPS) Technique is better than writing descriptive texts without Think Pair Share (TPS) Technique. Keyword: Descriptive text, Think Pair Share (TPS) technique, Writing skill